Brachial plexopathy after prone positioning - Goettler, Claudia E.; Pryor, John P.; Reilly, Patrick M. (East Carolina University, 2002)
Two cases of brachial plexus injury after prone position in the intensive care unit are described. Mechanisms of brachial plexus injury are described, as are methods for prevention of this unusual complication. Originally published in Critical Care, 2002 Vol. 6, No. 6.
Keywords: Adult respiratory distress syndrome; Branchial plexopathy; Prone position